Pajak Penghasilan Orang Pribadi Usaha Mikro dan Kecil di Indonesia: Kebijakan dan Implikasi - Fany Inasius (Bina Nusantara University, 2015)
Income Tax, whether it is personal or business entities taxpayers, with circulation up to 4.8billion rupiah is 1 percent and the final since July 1, 2013 according to the Government Regulation number 46 year of 2013 (PP46). This paper analyzes the implications of this regulation for micro and small businesses taxpayer with the category of gross circulation to 600 million rupiah. From the research that is conducted by the method of comparative research, descriptive and document analysis, it is showed that this regulation can reduce the compliance cost due to the simplicity of the calculation. However, the imposition of income tax according to the PP 46 is higher than before this regulation is applied for personal entities taxpayer of micro and small business with a turn over up to 600 million rupiah. On the other hand, for personal entities taxpayer of middle business, with the highest circulation, the imposition of income tax is lower